Scrawl : a novel - Shulman, Mark, 1962- (Roaring Brook Press, 2010)
When eighth-grade school bully Tod and his friends get caught committing a crime on school property, his penalty--staying after school and writing in a journal under the eye of the school guidance counselor--reveals aspects of himself that he prefers to keep hidden.